Managing brands in 4D : understanding perceptual, emotional, social and cultural branding - Pogorzelski, Jacek (Emerald Publishing Limited, 2018)
Brand is not an image or an idea, brand is associations or memory, feelings or emotions, attitudes, beliefs, and values, and experiences and lifestyles. Brand belongs to all of these categories, but the existing brand models almost all work under the assumption that there is only one type of brand, preventing true successful brand creation. Here Pogorzelski dives into the four methods and levels that organize the world of brand management, showcasing the research and tools needed to not only entice purchases, but create ideologies and support a specific lifestyle and culture, leading to true successful brands.
Includes index.
Keywords: Brand name products -- Management.; Branding (Marketing); Business & Economics -- Advertising & Promotion.; Business & management.; elektronické knihy; electronic books